2011
DOI: 10.1007/s10549-011-1714-9
|View full text |Cite
|
Sign up to set email alerts
|

Baseline diastolic dysfunction as a predictive factor of trastuzumab-mediated cardiotoxicity after adjuvant anthracycline therapy in breast cancer

Abstract: To evaluate the interest in assessing left ventricular diastolic function at baseline for prediction of trastuzumab-mediated cardiotoxicity (TMC) in the setting of adjuvant treatment for breast cancer. The study included 118 women presenting with HER2-positive early-stage invasive breast cancer. Patients received trastuzumab therapy over 1 year, concurrent with six cycles of docetaxel (n = 53), or following anthracycline-based chemotherapy with a cumulative dose of 300 mg/m(2) (n = 45) or 600 mg/m(2) (n = 20) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 51 publications
1
62
0
2
Order By: Relevance
“…These results support the hypothesis that DD is the earliest manifestation of cardiotoxicity from cancer drugs. Postchemotherapy injuries, such as left thorax irradiation or administration of the anti-Erbb2 monoclonal antibody, trastuzumab, might cause DD to progress toward systolic dysfunction [27]. Developing comorbidities, which tend to accumulate in cancer survivors, might also build on DD to precipitate late cardiac events [4].…”
Section: Discussionmentioning
confidence: 99%
“…These results support the hypothesis that DD is the earliest manifestation of cardiotoxicity from cancer drugs. Postchemotherapy injuries, such as left thorax irradiation or administration of the anti-Erbb2 monoclonal antibody, trastuzumab, might cause DD to progress toward systolic dysfunction [27]. Developing comorbidities, which tend to accumulate in cancer survivors, might also build on DD to precipitate late cardiac events [4].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found a higher prevalence of LVDD in patients receiving concurrent treatment than RT alone, although the difference was not statistically significant (35.2% versus 19.7%, p 5 .061). The major mechanism proposed for trastuzumab-associated cardiac toxicity is that blocking HER2 has a negative impact on the response of the heart to stress and myocardial damage [28,29]. Lack of resistance to stresses within the HER2-blocked myocardium may lead to amplified signs of injury, especially when cardiotoxic agents, such as anthracycline and irradiation, are administered in combination with trastuzumab [28,30].…”
mentioning
confidence: 99%
“…In particular, a previous cumulative dose >240 mg/m(2) of doxorubicin or >500 mg/m(2) of epirubicin increases the risk 3-fold compared with lower doses. (62) (63) Diastolic function assessment after completion of the anthracycline-containing elements of current treatment protocols might be an integrative index of the risk for trastuzumab-induced cardiotoxicity based on prior chemotherapy and cardiovascular risk factors. (63) The value of baseline strain imaging has not been studied so far.…”
Section: Cardiotoxicitymentioning
confidence: 99%